Preparation method and application of super-hydrophobic silica fume
Through chemical modification of silicon fumes such as silane coupling agents, superhydrophobic silicon fumes that can be used in cement-based materials and coatings were prepared, which solved the problem that existing modified silicon fume materials could not be used as coating materials, and improved cement The hydrophobicity and corrosion resistance of the base material reduce the production cost and safety risks.
Patent Information
- Application Number
- CN202411370607.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-01-03
AI Technical Summary
The existing modified silica fume material cannot be used as a coating material, and when used as a blend, the cement-based material still has high water absorption and low corrosion resistance, and the preparation method is high, the raw materials are expensive and unsafe. .
The silane coupling agent, nonionic surfactant and acidic alcohol solvent are mixed, and then reacted with fume and water to prepare superhydrophobic fume. This fume can be used as a blend in cement-based materials, as well as It can be used as a coating material and modified with a silane coupling agent to reduce its water absorption and improve corrosion resistance.
The application of superhydrophobic silicon fume as a coating material is realized, which reduces the water absorption rate of cement-based materials, improves corrosion resistance, and reduces the preparation cost, and is safe and environmentally friendly.
Smart Images

Figure CN119241109A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of super-hydrophobic materials, and in particular to a preparation method and application of super-hydrophobic silica fume. Background Art
[0002] Silica fume comes from industrial fields such as steel, aluminum electrolysis, coking, and cement, especially in the smelting process of metallic silicon and silicon alloys. These processes will produce a large amount of flue gas. After the flue gas is purified by control equipment, silica fume solid waste will be obtained. Although silica fume belongs to solid waste, it contains a large amount of resources such as silicon dioxide and aluminum, and has the potential for recycling and reuse. Through effective resource utilization, the impact of silica fume solid waste on the environment can be reduced and the goal of sustainable development can be achieved. In addition, in the field of cement-based materials, cement is the main source of carbon emissions, and about 1 ton of carbon dioxide is released for every ton of cement produced. Therefore, reducing the amount of cement used is an effective way to reduce carbon emissions in the field of cement-based materials. In recent years, modified nano-additives are usually introduced to optimize the mix ratio of the main solid waste raw materials to improve the performance of concrete and reduce carbon emissions. However, due to the hydrophilicity and porosity of the surface of cement-based materials, the corrosive ions carried by external water can easily penetrate into the material and cause corrosion damage to the cement-based materials. Especially in cold winter, when water penetrates the pores inside the mortar and repeatedly transitions between ice and water, the pressure in the pores will increase and the structure will be damaged. In order to reduce the damage of corrosive ions to the mortar, water seepage must be effectively prevented. The existing methods to prevent water seepage mainly use super-hydrophobic surface technology, and there are two main ways: one is to prepare a protective coating on the surface of cement-based materials, and the other is to improve the overall hydrophobicity of cement-based materials. Based on this, the fineness and specific surface area of silica fume are about 80 to 100 times that of cement. After adding it to cement-based materials, it can effectively fill the pores of cement-based materials, increase the density of cement, and thus improve the overall hydrophobicity of cement-based materials.
[0003] There are related studies on adding silica fume to cement-based materials in the prior art. For example, the Chinese invention patent with patent number CN112939499A discloses a method for preparing a modified silica fume material, in which silica fume is added to anhydrous ethanol, and a silane coupling agent is used to perform surface chemical modification on the silica fume to obtain a modified silica fume material, and then the modified silica fume is added to fly ash cement to improve the fluidity of the fly ash cement paste. However, this method improves the hydrophobicity of cement-based materials by replacing mineral admixtures in cement with modified silica fume, and cannot be used as a coating material. The Chinese invention patent with patent number CN117361921A discloses a modified silica fume and its preparation method, and ultra-high performance concrete. Three aminosilane modifiers (aminopropyl trimethoxysilane, aminopropyl triethoxysilane and glycidyl ether oxypropyl trimethoxysilane) are used to modify and grind silica fume to obtain modified silica fume, which is then added to the high-performance concrete slurry to improve the working performance (expansion) and strength of the ultra-high performance concrete. This method also improves the hydrophobicity of cement-based materials by replacing mineral admixtures in cement with modified silica fume, and cannot be used as a coating material. Moreover, after the modified silica fume is added to the cement-based material as a mineral admixture, the obtained cement-based material still has a high water absorption rate and a low anti-corrosion performance.
[0004] Therefore, there is an urgent need to provide a method for preparing super-hydrophobic silica fume which can be used as an admixture in cement-based materials and as a coating material, so as to solve the problem that the existing modified silica fume materials cannot be used as coating materials and the cement-based materials obtained when the existing modified silica fume is used as an admixture still have a high water absorption rate and low anti-corrosion performance, and at the same time solve the problem that the existing method for preparing modified silica fume materials is high in cost, and the raw materials are expensive and unsafe. Summary of the invention
[0005] In view of this, the present invention provides a preparation method and application of super-hydrophobic silica fume to solve the problem that the existing modified silica fume material cannot be used as a coating material and the cement-based material obtained when the existing modified silica fume is used as an admixture still has a high water absorption rate and low anti-corrosion performance, and at the same time solves the problem that the existing method for preparing modified silica fume materials is high in cost, and the raw materials are expensive and unsafe.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The present invention provides a method for preparing super-hydrophobic silica fume, comprising the following steps:
[0008] 1) mixing a silane coupling agent, a nonionic surfactant, and an acidic alcohol solvent to obtain a solution A;
[0009] 2) mixing silica fume with water to obtain dispersion B;
[0010] 3) mixing solution A and dispersion B, reacting to obtain super-hydrophobic silica fume;
[0011] There is no order restriction for step 1) and step 2).
[0012] Preferably, in step 1), the volume ratio of the silane coupling agent, the nonionic surfactant and the acidic alcohol solvent is 9-12:1.5-2:10-15; the pH value of the acidic alcohol solvent is 4-5.
[0013] Preferably, the mixing temperature in step 1) is 40-50°C.
[0014] Preferably, the silane coupling agent in step 1) includes n-octyltriethoxysilane and / or methyltrimethoxysilane; the nonionic surfactant includes one or more of Triton X-100, Triton X-165, Triton X-305, Triton X-405 and Triton X-705; the preparation step of the acidic alcohol solvent is: mixing a pH regulator with an alcohol to obtain an acidic alcohol solvent; the alcohol includes one or more of methanol, ethanol, propanol and butanol; the pH regulator includes one or more of acetic acid, formic acid and phosphoric acid.
[0015] Preferably, the mass ratio of silica fume to water in step 2) is 3-5:4-6.
[0016] Preferably, in step 3), the volume ratio of solution A to dispersion B is 21-30:70-110.
[0017] Preferably, the reaction temperature in step 3) is 65-85° C., and the reaction time is 0.5-2 h.
[0018] The present invention also provides super-hydrophobic silica fume prepared by the above-mentioned super-hydrophobic silica fume preparation method, wherein the contact angle of the super-hydrophobic silica fume is ≥151°.
[0019] The present invention also provides an application of the super-hydrophobic silica fume as a coating material.
[0020] The present invention also provides an application of the super-hydrophobic silica fume as an admixture in cement-based materials.
[0021] It can be seen from the above technical solution that compared with the prior art, the present invention has the following beneficial effects:
[0022] Super-hydrophobic silica fume of the present invention can be used as mineral admixture to replace cement, and can also be directly sprayed on fresh concrete surface to obtain super-hydrophobic self-cleaning inorganic coating after solidification, and is used as coating material, and solves the problem that existing super-hydrophobic silica fume can not be used as coating material, and compared to modified silica fume material in the prior art, when super-hydrophobic silica fume of the present invention is mixed in cement-based material as mineral admixture, the water absorption rate of cement-based material can also be reduced, and the anticorrosive property of cement-based material is improved, so that cement-based material has better hydrophobicity and anticorrosive property. Meanwhile, the preparation method cost of super-hydrophobic silica fume of the present invention is low, and raw materials are cheap, safe and green and environmentally friendly. In addition, super-hydrophobic silica fume of the present invention can also be used in combination with a variety of commercial adhesives, and is conducive to increasing the bonding force of super-hydrophobic surface and substrate, so that the super-hydrophobic silica fume has a wide range of applications. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying creative work.
[0024] Figure 1 The super-hydrophobic silica ash prepared in Example 1 and the SEM-EDS analysis diagram of the silica ash, wherein: Figure 1 a in the figure is the SEM image of the super-hydrophobic silica ash prepared in Example 1, Figure 1 b is the SEM image of silica fume. Figure 1 c in the figure is the EDS image of the super-hydrophobic silica ash prepared in Example 1, Figure 1 Figure d is the EDS image of silica fume;
[0025] Figure 2 The super-hydrophobic silica fume and the XRD pattern of the silica fume prepared in Example 1;
[0026] Figure 3 The super-hydrophobic silica fume prepared in Example 1 and the FTIR spectrum of the silica fume;
[0027] Figure 4 The static wettability diagram of the super-hydrophobic silica ash and silica ash prepared in Example 1, wherein: Figure 4 a in the figure is the static wettability diagram of the super-hydrophobic silica fume prepared in Example 1, Figure 4 b in the figure is the static wettability diagram of silica fume;
[0028] Figure 5 The static wettability diagram of the super hydrophobic slurry and the ordinary slurry prepared in Application Example 1, wherein: Figure 5 a in the figure is the static wettability diagram of the super hydrophobic slurry prepared in Application Example 1. Figure 5 b in the figure is the static wettability diagram of ordinary pure slurry;
[0029] Figure 6 The water absorption rate diagram of the super hydrophobic slurry and the ordinary slurry prepared in Application Examples 1 to 3;
[0030] Figure 7 The Tafel diagrams of the super-hydrophobic slurry and the ordinary slurry prepared in Application Examples 1 to 3;
[0031] Figure 8 The EIS graphs of the super-hydrophobic slurry and the ordinary slurry prepared in Application Examples 1 to 3;
[0032] Fig. 9 This is the static wettability diagram of the superhydrophobic self-cleaning inorganic coating prepared in Application Example 4. DETAILED DESCRIPTION
[0033] The present invention provides a method for preparing super-hydrophobic silica fume, comprising the following steps:
[0034] 1) mixing a silane coupling agent, a nonionic surfactant, and an acidic alcohol solvent to obtain a solution A;
[0035] 2) mixing silica fume with water to obtain dispersion B;
[0036] 3) mixing solution A and dispersion B, reacting to obtain super-hydrophobic silica fume;
[0037] There is no order restriction for step 1) and step 2).
[0038] In the present invention, the mixing in step 1) is preferably: in a water bath, a pH adjuster is added to an acidic alcohol solvent, and then a silane coupling agent and a nonionic surfactant are added in sequence until the solution becomes clear, which is regarded as the end point of dissolution.
[0039] In the present invention, the silane coupling agent in step 1) is preferably added in multiple times, and the interval time of each addition is preferably 2 to 6 minutes, more preferably 4 to 5.5 minutes, and more preferably 5 minutes; the volume of each addition is preferably 1 to 2.5 mL, more preferably 1.2 to 2.3 mL, and more preferably 2 mL.
[0040] In the present invention, the volume ratio of the silane coupling agent, the nonionic surfactant and the acidic alcohol solvent in step 1) is preferably 9-12:1.5-2:10-15, more preferably 9.5-10.5:1.6-1.8:10.5-13, and more preferably 10:1.7:11.
[0041] In the present invention, the pH value of the acidic alcohol solvent is 4 to 5, more preferably 4.2 to 4.8, and more preferably 4.5.
[0042] In the present invention, the mixing temperature (water bath temperature) in step 1) is 40-50°C, more preferably 42-48°C, and more preferably 45°C.
[0043] In the present invention, the silane coupling agent in step 1) includes n-octyltriethoxysilane and / or methyltrimethoxysilane; the nonionic surfactant includes one or more of Triton X-100, Triton X-165, Triton X-305, Triton X-405 and Triton X-705; the preparation step of the acidic alcohol solvent is: mixing a pH regulator with an alcohol to obtain an acidic alcohol solvent; the alcohol includes one or more of methanol, ethanol, propanol and butanol; the pH regulator includes one or more of acetic acid, formic acid and phosphoric acid.
[0044] In the present invention, the mass ratio of the silica ash to water in step 2) is 3-5:4-6, further preferably 3.5-4.5:4.5-5.5, and more preferably 4:5; the content of SiO2 in the silica ash is preferably greater than 95%, more preferably greater than 97%; the silica ash is preferably purchased from Henan Yixiang New Materials Co., Ltd.
[0045] In the present invention, the mixing speed in step 2) is 190-210 r / min, more preferably 195-205 r / min, more preferably 200 r / min; the mixing time is 1-3 h, more preferably 1.5-2.5 h, more preferably 2 h.
[0046] In the present invention, the volume ratio of solution A to dispersion B in step 3) is 21-30:70-110, more preferably 22-28:80-105, and more preferably 23-25:90-100.
[0047] In the present invention, the reaction temperature in step 3) is 65-85°C, more preferably 70-83°C, more preferably 80°C; the reaction time is 0.5-2h, more preferably 1-1.8h, more preferably 1.2-1.5h.
[0048] In the present invention, after the solution A and the dispersion B are mixed, the processes of sealing, aging, drying and grinding are sequentially included.
[0049] In the present invention, the sealed aging temperature is preferably 20-35°C, more preferably 22-32°C, and more preferably 25-30°C; the sealed aging time is preferably 2-6h, more preferably 3-5h, and more preferably 4h.
[0050] In the present invention, the drying temperature is preferably 75-85°C, more preferably 77-83°C, and even more preferably 80°C.
[0051] In the present invention, the particle size after grinding is preferably ≤1000 nm.
[0052] The present invention also provides super-hydrophobic silica fume prepared by the preparation method of the super-hydrophobic silica fume, wherein the contact angle of the super-hydrophobic silica fume is ≥151°.
[0053] The present invention also provides an application of the super-hydrophobic silica fume as a coating material.
[0054] The present invention also provides an application of the super-hydrophobic silica fume as an admixture in a cement-based material.
[0055] In the present invention, the mass percentage of super hydrophobic silica fume in the cement-based material is preferably 2-6%.
[0056] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0057] Example 1
[0058] 1) The temperature of the magnetic stirring water bath was controlled at 50°C, then 12 mL of methanol was put into a conical flask and placed on the magnetic stirring water bath, acetic acid was added dropwise to adjust the pH to 4.5, then 12 mL of n-octyltriethoxysilane was added to the conical flask every 5 minutes, and 1.5 mL of Triton X-100 was added while stirring to mix, and the solution was considered to be completely dissolved when it was clear, thus obtaining solution A;
[0059] 2) Mix silica fume and deionized water in a mass ratio of 4:5 and stir on an electric stirrer at a speed of 200 r / min for 2 h to obtain dispersion B;
[0060] 3) 25.5 mL of solution A and 90 mL of dispersion B were reacted at 80° C. for 2 h, then sealed and aged at 35° C. for 2 h, and then dried in a constant temperature drying oven controlled at 80° C., and finally pulverized by an air flow ultrafine grinder to obtain super-hydrophobic silica ash with a particle size of ≤1000 nm.
[0061] The SEM-EDS analysis diagram of the super-hydrophobic silica fume and silica fume (original silica fume purchased from Henan Yixiang New Materials Co., Ltd.) obtained in this example is as follows: Figure 1 As shown, from Figure 1 As can be seen from a in the figure, the super hydrophobic silica fume has particles with a roughness of micrometer / nanometer size; Figure 1From c and d in the figure, it can be seen that the EDS spectra of the modified super-hydrophobic silica fume and the original silica fume before modification mainly have carbon (C), oxygen (O) and silicon (Si) element peaks. Among them, the large distribution of C element indicates that there are C-containing substances on the surface of the silica fume before and after modification. The C element in the super-hydrophobic silica fume mainly comes from -CH3 in silane. These grafted hydrophobic groups replace the -OH on the surface of the silica fume and cause a decrease in surface energy, which is the basis for the construction of the super-hydrophobic surface.
[0062] The XRD patterns of the super-hydrophobic silica fume and the original silica fume obtained in this embodiment are as follows: Figure 2 As shown, from Figure 2 It can be seen that the XRD spectrum curves of the original silica fume and the super-hydrophobic silica fume are basically overlapped, and only the dispersion peak of the amorphous phase appears near 2θ=22°, indicating that the surface modification method of silica fume described in the present invention does not significantly affect the physical phase composition of the silica fume itself. In addition, both the silica fume and the super-hydrophobic silica fume have weak diffraction peaks, which may be the characteristic peaks of impurities in the silica fume.
[0063] The FTIR spectra of the super-hydrophobic silica fume and the original silica fume obtained in this example are as follows: Figure 3 As shown, from Figure 3 It can be seen that the chemical groups of super-hydrophobic silica fume and SiO2 are basically the same, 3450cm -1 The peak at 2970cm is the stretching vibration absorption peak of the OH bond of water adsorbed on the surface of silica fume. Among them, the peak intensity of the original silica fume is significantly higher than that of the super-hydrophobic silica fume, which confirms that the surface modification of the super-hydrophobic silica fume is completed by condensing the silane chain on the surface of the silica fume by hydroxyl groups. -1 、2930cm -1 and 2850cm -1 The absorption peak intensity at 1630cm is significantly increased, which is caused by the stretching vibration absorption peak of the CH bond on the silane, indicating that the hydrophobic group has been successfully condensed on the surface of the silica fume. -1 The peak at 1120cm is the bending vibration absorption peak of the OH bond of water adsorbed on the surface of silica fume. At this time, the original silica fume has a higher peak intensity than the super-hydrophobic silica fume, which may be due to the hydrolysis of silane leading to the formation of -OH and other hydrophilic groups that may absorb atmospheric water. -1 The antisymmetric stretching vibration absorption peak of Si-O-Si bond is 801cm -1 It is the symmetrical stretching vibration absorption peak of Si-O bond on silica fume and silane. It can be seen that due to the addition of silane coupling agent, the absorption peak intensity of Si-O-Si bond and Si-O bond of the modified superhydrophobic silica fume is significantly enhanced, indicating that the number of bonds after modification is significantly increased.
[0064] The static wettability images of the super-hydrophobic silica fume obtained in this example and the original silica fume are shown in FIG. Figure 4As shown, from Figure 4 It can be seen that the water droplets on the surface of super-hydrophobic silica ash are spherical and have good super-hydrophobicity.
[0065] Example 2
[0066] 1) The temperature of the magnetic stirring water bath was controlled at 40°C, then 10 mL of methanol was put into a conical flask and placed on the magnetic stirring water bath, acetic acid was added dropwise to adjust the pH to 4, then 10 mL of methyltrimethoxysilane was added to the conical flask every 5 minutes, and 1.5 mL of Triton X-100 was added while stirring to mix, and the solution was considered to be completely dissolved when it was clear, thus obtaining solution A;
[0067] 2) Mix silica fume and deionized water in a mass ratio of 5:4 and stir on an electric stirrer at a speed of 190 r / min for 2 h to obtain dispersion B;
[0068] 3) 21 mL of solution A and 70 mL of dispersion B were mixed and stirred at 65 ° C for 2 h, then sealed and aged at 25 ° C for 2 h, and then placed in a constant temperature drying oven controlled at 80 ° C for drying, and finally pulverized by an air flow ultrafine grinder to obtain super hydrophobic silica ash with a particle size of ≤1000 nm.
[0069] Example 3
[0070] 1) The temperature of the magnetic stirring water bath was controlled at 40°C, then 14 mL of methanol was taken into a conical flask and placed on the magnetic stirring water bath, acetic acid was added dropwise to adjust the pH to 4, then 12 mL of methyltrimethoxysilane was added to the conical flask every 5 minutes, and 2 mL of Triton X-100 was added while stirring to mix. When the solution was clear, the solution was considered to be completely dissolved, thereby obtaining Solution A;
[0071] 2) Mix silica fume and deionized water in a mass ratio of 5:4 and stir on an electric stirrer at a speed of 210 r / min for 2 h to obtain dispersion B;
[0072] 3) 60 mL of solution A and 220 mL of dispersion B were mixed and stirred at 65 ° C for 2 h, then sealed and aged at 30 ° C for 2 h, and then placed in a constant temperature drying oven controlled at 80 ° C for drying, and finally pulverized by an air flow ultrafine grinder to obtain super hydrophobic silica ash with a particle size of ≤1000 nm.
[0073] Example 4
[0074] 1) The temperature of the magnetic stirring water bath was controlled at 45°C, then 10 mL of ethanol was put into a conical flask and placed on the magnetic stirring water bath, formic acid was added dropwise to adjust the pH to 5, then 9 mL of n-octyltriethoxysilane was added to the conical flask at 2 mL intervals of 5 min, and at the same time, 1.8 mL of Triton X-165 was added while stirring to mix, and the solution was considered to be completely dissolved when it was clear, thereby obtaining solution A;
[0075] 2) Mix silica fume and deionized water in a mass ratio of 1:2 and stir on an electric stirrer at a speed of 190 r / min for 3 h to obtain dispersion B;
[0076] 3) 42 mL of solution A and 140 mL of dispersion B were mixed and stirred at 70 ° C for 1.5 h, then sealed and aged at 20 ° C for 5 h, and then placed in a constant temperature drying oven controlled at 85 ° C for drying, and finally pulverized by an air flow ultrafine grinder to obtain super hydrophobic silica ash with a particle size of ≤1000 nm.
[0077] Example 5
[0078] 1) The temperature of the magnetic stirring water bath was controlled at 45°C, then 11 mL of propanol was put into a conical flask and placed on the magnetic stirring water bath, phosphoric acid was added dropwise to adjust the pH to 4.5, then 10 mL of methyltrimethoxysilane was added to the conical flask at 2 mL intervals of 5 min, and at the same time, 1.7 mL of Triton X-305 was added while stirring to mix, and the solution was considered to be completely dissolved when it was clear, thus obtaining solution A;
[0079] 2) Mix silica fume and deionized water in a mass ratio of 4:5 and stir on an electric stirrer at a speed of 210 r / min for 1 h to obtain dispersion B;
[0080] 3) 30 mL of solution A and 110 mL of dispersion B were mixed and stirred at a temperature of 85° C. for 0.5 h, then sealed and aged at a temperature of 35° C. for 3 h, and then placed in a constant temperature drying oven controlled at 75° C. for drying, and finally pulverized by an air flow ultrafine grinder to obtain super-hydrophobic silica ash with a particle size of ≤1000 nm.
[0081] Application Example 1
[0082] The superhydrophobic silica fume prepared in Example 2 replaces 6% of cement to prepare superhydrophobic slurry. The specific preparation steps of the superhydrophobic slurry are: 376 parts of cement, 24 parts of superhydrophobic silica fume and 120 parts of water are mixed evenly to obtain superhydrophobic slurry (6% superhydrophobic silica fume).
[0083] The static wettability image of the super hydrophobic slurry prepared in Application Example 1 and the static wettability image of the ordinary slurry are as follows: Figure 5 As shown, from Figure 5It can be observed that the superhydrophobic slurry modified with silane surface exhibits strong hydrophobicity, and water droplets cannot spread on the material, presenting a nearly spherical state.
[0084] Application Example 2
[0085] The superhydrophobic silica fume prepared in Example 2 is used to replace 2% of cement to prepare superhydrophobic slurry. The specific preparation steps of the superhydrophobic slurry are: 392 parts of cement, 8 parts of superhydrophobic silica fume and 120 parts of water are mixed evenly to obtain superhydrophobic slurry (2% superhydrophobic silica fume).
[0086] Application Example 3
[0087] The superhydrophobic silica fume prepared in Example 2 replaces 4% of cement to prepare superhydrophobic slurry. The specific preparation steps of the superhydrophobic slurry are: 384 parts of cement, 16 parts of superhydrophobic silica fume and 124 parts of water are mixed evenly to obtain superhydrophobic slurry (4% superhydrophobic silica fume).
[0088] After testing, the water absorption rates of the super-hydrophobic slurry prepared in Application Examples 1 to 3 and the ordinary slurry (blank group, the difference between the blank group and Application Examples 1 to 3 is that the super-hydrophobic silica fume is not used to replace cement) are as follows: Figure 6 As shown, from Figure 6 It can be seen that when super-hydrophobic silica fume replaces part of the cement, the super-hydrophobic paste has extremely strong hydrophobicity, which means that it is more difficult for water to spread and penetrate on the surface of the material, thereby reducing the water absorption rate. There is also a negative correlation between the amount of super-hydrophobic silica fume and the water absorption rate. This is mainly because the more super-hydrophobic silica fume is added, the more hydrophobic groups are combined with cement-based materials, which enhances the paste's repellency to water and prevents more water from entering.
[0089] The Tafel diagrams of the super hydrophobic slurry prepared in Application Examples 1 to 3 and the ordinary slurry (blank group) are shown in FIG. Figure 7 As shown, from Figure 7 It can be seen that the polarization curve of the superhydrophobic paste after adding superhydrophobic silica fume moves to the left, reflecting the effect of superhydrophobic paste on Cl - This is attributed to the hydrophobic layer constructed by hydrophobic silica fume on the surface of the slurry, which effectively blocks water penetration and significantly reduces the water absorption of the slurry layer, thereby slowing down the Cl carried by water. - It can effectively protect the internal steel bars from corrosion.
[0090] The EIS graphs of the super hydrophobic slurry prepared in Application Examples 1 to 3 and the ordinary slurry (blank group) are as follows: Figure 8 As shown, from Figure 8 It can be seen that with the increase of super-hydrophobic silica fume content, the capacitance arc diameter in the high-frequency and low-frequency regions gradually increases, reflecting that the super-hydrophobic slurry exhibits better anti-corrosion performance.
[0091] Application Example 4
[0092] The super-hydrophobic silica fume prepared in Example 3 is directly sprayed on the surface of fresh concrete using a powder spraying device, and then cured to obtain a super-hydrophobic self-cleaning inorganic coating.
[0093] The static wettability diagram of the super hydrophobic self-cleaning inorganic coating prepared in Application Example 4 is as follows: Fig. 9 As shown, from Fig. 9 It can be observed that the coating surface has micro-nano rough particles, the coating surface adhesion is extremely low, and the water droplets appear in a spherical state on the coating surface.
[0094] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing super-hydrophobic silica fume, characterized in that: The steps include: 1) mixing a silane coupling agent, a nonionic surfactant, and an acidic alcohol solvent to obtain a solution A; 2) mixing silica fume with water to obtain dispersion B; 3) mixing solution A and dispersion B, reacting to obtain super-hydrophobic silica fume; There is no order restriction for step 1) and step 2).
2. A method for preparing super hydrophobic silica ash according to claim 1, characterized in that, The volume ratio of the silane coupling agent, the nonionic surfactant and the acidic alcohol solvent in step 1) is 9-12:1.5-2:10-15; The pH value of the acidic alcohol solvent is 4-5.
3. A method for preparing super hydrophobic silica ash according to claim 2, characterized in that, The mixing temperature in step 1) is 40-50°C.
4. A method for preparing super-hydrophobic silica fume according to any one of claims 1 to 3, characterized in that: The silane coupling agent in step 1) includes n-octyltriethoxysilane and / or methyltrimethoxysilane; The nonionic surfactant includes one or more of Triton X-100, Triton X-165, Triton X-305, Triton X-405 and Triton X-705; The preparation steps of the acidic alcohol solvent are: mixing a pH value adjuster with alcohol to obtain an acidic alcohol solvent; The alcohol includes one or more of methanol, ethanol, propanol and butanol; The pH adjuster includes one or more of acetic acid, formic acid and phosphoric acid.
5. A method for preparing super hydrophobic silica ash according to claim 4, characterized in that, The mass ratio of silica fume to water in step 2) is 3-5:4-6.
6. A method for preparing super hydrophobic silica fume according to claim 5, characterized in that, In step 3), the volume ratio of solution A to dispersion B is 21-30:70-110.
7. A method for preparing super hydrophobic silica fume according to claim 6, characterized in that, The reaction temperature in step 3) is 65-85°C, and the reaction time is 0.5-2h.
8. The super-hydrophobic silica fume prepared by the method for preparing super-hydrophobic silica fume according to any one of claims 1 to 7, characterized in that: The contact angle of the super-hydrophobic silica fume is ≥151°.
9. application of the super-hydrophobic silica ash described in claim 8 as coating material.
10. Application of the super-hydrophobic silica fume according to claim 8 as an admixture in cement-based materials.
